The Method of Dirichlet Generating Series in the Theory of Distribution of Additive Arithmetic Functions. II - Kubilius, J. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Кубилюс. Метод производящих рядов Дирихле в теории распределения аддитивных арифметических функций. II J. Kubilius. Generuojančių Dirichlė eilučių metodas adityvinių aritmetinių funkcijų pasiskirstymo teorijoje. II